Oxybutynin-Nanoemulgel Formulation as a Successful Skin Permeation Strategy: In-vitro and ex-vivo Evaluation - Mohammadi-Samani, Soliman; Masoumzadeh, Pedram; Ghasemiyeh, Parisa; Alipour, Shohreh (Frontiers in Materials, 2022)
Among different topical drug delivery systems, nanoemulsions (NEs) are attractive due to enhanced skin permeation potential and minimum toxicity. Topical nanoemulgels (NEMGELs) contain both gelling agents and NEs and thus can enhance skin permeation with sustained effects at the site of application. Oxybutynin (OXB) is an anti-muscarinic agent that is administered orally to treat hyperhidrosis but its systemic side effects may decrease patient compliance. Therefore, it assumes that oxybutynin-nanoemulgel (OXB-NEMGEL) with sustained release properties and skin permeation ability may be a suitable alternative. Using Design Expert software®, 17 OXB-NE formulations were prepared and optimized based on particle size, zeta potential and physical stability. Three polymers were used to prepare and optimized OXB-NEMGEL based on spreadability and viscosity. In-vitro drug release and ex-vivo skin permeation were investigated for optimized formulation. The model suggested by Design-Expert was quadratic and there was significant association between response variables including particle size and zeta potential and independent variables (Oil:Surfactant ratio, Oil:Water ratio, and surfactants HLB) with P-values of 0.0334 and 0.0173, respectively. Also, the lack of fit was not significant (P-values 0.057 and 0.569, respectively) which confirms the fitness of this model. Average size and zeta potential of optimized nanoemulsions were 99 ± 0.1 nm and -57.3 ± 0.5 mv, respectively. Carboxymethyl cellulose-based nanoemulgels (CMC-NEMGEL) showed acceptable viscosity with a shear thinning rheological pattern and good spreadability which released OXB within 8 h. Ex-vivo OXB skin permeation revealed OXB flux of 1.5 ± 0.3 and 3.6 ± 0.2 μg/cm2/h after 12 and 24 h, respectively, which was equal to 5.3 ± 1.1% and 11.9 ± 0.7% of drug, while simple OXB gel did not permeate through skin layers. Thus, OXB-NEMGEL with effective skin permeation potential would be a novel promising drug delivery system for hyperhidrosis management which may lower systemic side effects.